Corporate Social Responsibility and Firm Value: An Empirical Study of Listed Transport Company in Vietnam - Le Xuan Quynh Tran Thị Cam Thanh (My University, 2019)
Corporate Social Responsibility and Firm Value: An Empirical Study of Listed Transport Company in Vietnam
Keywords: CSR; Firm Value; Transport Company